Co-pyrolysis of sewage sludge and cotton stalks. (15th April 2019) - Wang, Zhipu; Xie, Like; Liu, Kai; Wang, Jian; Zhu, Henan; Song, Qiang; Shu, Xinqian
Highlights: Biochars obtained were rich in plant nutrients. Specific surface areas of the biochars were significantly increased. Heavy metals were immobilized in the biochars. Abstract: Proper disposal of ever-increasing amounts sewage sludge and cotton stalks is a challenge around the world, and conversion of these wastes into biochars via co-pyrolysis may be a promising solution. In this study, biochars were prepared via co-pyrolysis of sewage sludge and cotton stalks with different mixing ratios (cotton stalks/sewage sludge, w/w) at 650 °C for 2.0 h, and then, biochars were characterized to identify their potential agronomic and environmental benefits as soil amendments. Biochars prepared with higher mixing ratios had higher C contents and lower H/C and N/C ratios, which suggests that this approach has potential for improving C storage in biochar-treated soils to help offset greenhouse gas emissions. All biochars were mesoporous materials with an average pore size of 3–4 nm. The specific surface area increases indicated that these biochars would have relatively high water holding capacities and heavy metal adsorption capacities in heavy metal contaminated soils. The high ash contents and cation exchange capacity values in biochars prepared with lower mixing ratios indicate that these products would be useful for enhancing the nutrient supply and nutrient retention capacity in degraded soils. Moreover, the addition of more cotton stalks efficiently decreased the mobility and bioavailability of heavy metals in the biochars. At a certain level, co-pyrolysis of sewage sludge and cotton stalks to produce biochars would have both economic and environmental benefits.